If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 8 + y Solving 7 = 8 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 7 + -1y = 8 + y + -1y Combine like terms: y + -1y = 0 7 + -1y = 8 + 0 7 + -1y = 8 Add '-7' to each side of the equation. 7 + -7 + -1y = 8 + -7 Combine like terms: 7 + -7 = 0 0 + -1y = 8 + -7 -1y = 8 + -7 Combine like terms: 8 + -7 = 1 -1y = 1 Divide each side by '-1'. y = -1 Simplifying y = -1
| t(x)=5x^2+4x | | 1=-4+4m+5 | | 4v+8=6(v+4) | | 114=39.95x | | 12x-6-6x-8=4-3x | | 5(3x-10)-5x=-15 | | 39=-3v | | 21x+3d=45 | | 7y^2-y+2=0 | | 19y-10=11y-2 | | 6.4=1.3-0.7y | | X+67+x+127=180 | | 36-7b=-3b(8b+5) | | 2y-3y+5y=42 | | 5h+4=3h+8 | | -54=9x | | 5m+4=-26 | | X^2/x-5 | | 5h+4=h+8 | | 11=x-12 | | 88+2x+62=2x+26 | | 4/(x-2)=6 | | 1.1x-3x=-34.3 | | 12-r=-8 | | 26=(5-x) | | -2(7u-2)+3u=1+2(2u-1) | | 40=2(x-4) | | -2=n+(-17) | | -5+.25c=15 | | 2x^2+3x+8=3x-10 | | 6x-1=133 | | v-(-10)=17 |